Developing an Anti-Racist Practice in Occupational Therapy: Guidance for the Occupational Therapist - Justin Lerner; Angie Kim, MA (Scholarworks @ WMU, 2022)
A strong anti-racist practice is critical for occupational therapists who represent an overwhelmingly white and female workforce yet serve people from all ethnic and racial backgrounds. These therapists are commonly unprepared to work with a racially diverse clientele because of a lack of reflective and critical practice grounded in anti-racism. This article provides some critical literature about race and racism in occupational science. We present important concepts for therapists to deepen their understanding of anti-racist practice, including intersectionality, agent and target groups, and equity and equality. We then explore some critical theoretical frameworks that can help conceptualize anti-racist practice, such as cycle of socialization, the 4 I's of oppression, window of tolerance, systems theory, cultural humility, and somatic racism. We conclude with intervention strategies informed by these frameworks that therapists can use to strengthen their anti-racist practice. These interventions include journaling, race caucusing, deepening relationships, deep listening, body awareness, and somatic healing. We hope that these concepts, critical frameworks, and intervention strategies can help occupational therapists develop a sustained anti-racist practice that will greatly benefit and support the people they serve.